Visual Identity Logo Collaboration Eiger 1989 x National Park Collection 2022 - Taufiq, Muhammad; Nalan, Arthur Supardan; Iskandar, Andang (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2023)
Every brand in the industry competition increasingly creates unlimited choices. That way, every brand is always trying to find ways to connect emotionally with consumers. Through this research, we can find out how the visual identity communicated through the collaboration logo design of the Eiger 1989 x National Park Collection is connected with the message of meaning to be conveyed. The research method uses qualitative to facilitate the analysis process. The authors also use a four-stage approach to visual communication design research methods, including description, analysis, interpretation, and assessment. The findings based on the research that has been done are collaboration logos that, at first glance, seem to use headlines with taglines. After being analyzed as a whole, the collaboration logo was designed based on following the anatomy of the logo formation, besides that, there are overall visual elements that can represent brand identity and collaboration concepts. Logo design through good composition and the meaning of good communication messages will increase customer loyalty.